FENOMENA GERAKAN HIJRAH DAN EKSTRIMISME PADA PEMUDA MUSLIM - Suhra Wardi,; Feriansyah,; Eddy Purnomo (Farabi, 2024)
This research seeks to examine a trending phenomenon in society: the hijrah movement and the rise of extreme ideology among youth. The study employs a literature review method, analyzing various sources such as reference books and prior research to establish a theoretical foundation for the investigated issue. The technique involves systematically describing and evaluating books, scholarly articles, notes, and relevant reports pertaining to the topic. The article explores a contemporary adult phenomenon gaining traction in society. In Indonesia, the hijrah movement manifests in two typologies: conservative and Islamist. This research draws on Islamic perspectives, particularly the views of communities promoting content that advocates specific practices—such as cutting men’s trousers (to modify clothing) and enforcing long headscarves and veils for women. Additionally, it addresses youth behaviors that contravene Islamic law, including criminal acts, out-of-wedlock pregnancies, drug abuse, and other social issues. From these observations, the study concludes that the youth hijrah movement has a largely positive impact, embodying Islamic religious values and promoting religious moderation. It also serves as a counter to extreme ideologies that disrupt societal harmony, positioning the Qur’an as a foundational guide for the movement’s development.